Analisis keputusan pembelian produk Skintific di TikTok Shop: Pengaruh influencer marketing, live shopping, dan FOMO - Nurjana, Anisa; Handayani, Susi; Yeni, Yeni (Journal of Management and Digital Business, 2026)
This study examines the influence of influencer marketing, live shopping, and fear of missing out (FOMO) on purchase decisions for Skintific products through TikTok Shop among students of the Faculty of Economics at Universitas Indo Global Mandiri. The research employed a quantitative, survey-based approach. Data were collected from respondents who had experience purchasing Skintific products via the TikTok Shop and were analyzed using multiple linear regression. The findings reveal that influencer marketing, live shopping, and fear of missing out each have a positive and significant effect on purchase decisions. These results indicate that digital marketing strategies supported by psychological consumer factors play a significant role in shaping purchasing behavior on social commerce platforms. This study also demonstrates that interactive shopping experiences and social influence can increase consumer interest and encourage purchasing decisions. The novelty of this research lies in integrating influencer marketing, live shopping, and fear of missing out within the TikTok Shop context, particularly among university students as digital consumers in emerging online marketplaces.